Fertility preservation and survival among young women with early ovarian cancer living in US counties with gynecologic oncologist services1. Issue 2 (24th February 2017) - Hillman, R. Tyler; Saenz, Cheryl C.; McHale, Michael T.; Plaxe, Steven C.
Abstract: Objective: To examine the association between living in a county with gynecologic oncologist provision, the performance of fertility sparing surgery, and survival among young women with early epithelial ovarian cancer. Methods: The present retrospective cohort study was based on the SEER 18 dataset of the US National Cancer Institute. Women younger than 45 years with early stage epithelial ovarian cancer diagnosed between 2000 and 2012 were included. Logistic regression and Cox proportional hazards methods were used to analyze all‐cause survival. Adjustment was made for relevant clinical and demographic variables. Results: In total, 1499 women were included. Women living in a county with gynecologic oncologist provision were less likely to undergo hysterectomy (adjusted odds ratio, 0.69; 95% confidence interval, 0.52–0.93) at the time of primary surgery. Women who underwent hysterectomy had a similar risk of mortality as women with uterine preservation (adjusted hazard ratio [HR], 0.73; 95% CI, 0.41–1.30). Living in a county with gynecologic oncologist provision was associated with reduced risk of mortality (adjusted HR, 0.53; 95% CI, 0.31–0.92). Conclusion: Living in a county with gynecologic oncologist provision was independently associated with the use of fertility sparing surgery among young women with early epithelial ovarian cancer. Abstract : Living in a US county with a gynecologic oncologist service is associated with use of fertility‐sparing surgery among young women with early epithelial ovarian cancer.